Pelayanan Prima dalam Pendidikan: Tinjauan Sistematis Tentang Strategi Meningkatkan Kepuasan Pelanggan dan Mutu Layanan - Umamul Muslikhin; St. Nur Azizah; Muhammad Taufiq Hidayatullah; Mu’alimin Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Service excellence has become a strategic issue in modern educational management because it is directly related to service quality, customer satisfaction, and the image of educational institutions. In the context of global competition and demands for public transparency, educational institutions are required to provide services that are effective, efficient, and oriented to the needs of students and the community. This study aims to systematically examine how the concept of service excellence is implemented in educational institutions and its impact on customer satisfaction. The method used was a systematic literature review, searching articles in national databases such as Google Scholar, Garuda, and campus journal portals using the keywords "service excellence," "service excellence," "education," and "customer satisfaction." Of the 20 articles found, seven met the analysis criteria. The results of the study revealed three main themes: improving the professionalism of educational staff, implementing the TQM concept in service, and strengthening a customer-oriented service culture. This literature synthesis concluded that service excellence significantly increases customer satisfaction and loyalty in educational institutions. Future research should focus on an integrative model of digital-based service excellence in educational institutions.